2022
DOI: 10.3233/jad-215448
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Metabolomic Analysis in Alzheimer’s Disease Plasma and Brain Tissue in Non-Hispanic Whites

Abstract: Background: Metabolites are biological compounds reflecting the functional activity of organs and tissues. Understanding metabolic changes in Alzheimer’s disease (AD) can provide insight into potential risk factors in this multifactorial disease and suggest new intervention strategies or improve non-invasive diagnosis. Objective: In this study, we searched for changes in AD metabolism in plasma and frontal brain cortex tissue samples and evaluated the performance of plasma measurements as biomarkers. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 92 publications
(86 reference statements)
2
26
2
Order By: Relevance
“…Previous studies have linked HHcy to changes in neuroimaging measures such as brain atrophy, white matter hyperintensities, and infarcts or cognitive performance, 30 , 31 while only a small number of studies have examined associations of HHcy with dementia‐related neuropathologies. 27 , 32 , 33 While there are a significant number of animal studies suggesting mechanisms for HHcy‐induced damage, there has been no robust human autopsy studies to evaluate these potential mechanisms. The present pilot study evaluated associations of HHcy with pathologic features in 31 autopsied research volunteers who had an ante mortem range of plasma tHcy from 4.8 to 27.3 µmol/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have linked HHcy to changes in neuroimaging measures such as brain atrophy, white matter hyperintensities, and infarcts or cognitive performance, 30 , 31 while only a small number of studies have examined associations of HHcy with dementia‐related neuropathologies. 27 , 32 , 33 While there are a significant number of animal studies suggesting mechanisms for HHcy‐induced damage, there has been no robust human autopsy studies to evaluate these potential mechanisms. The present pilot study evaluated associations of HHcy with pathologic features in 31 autopsied research volunteers who had an ante mortem range of plasma tHcy from 4.8 to 27.3 µmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhomocysteinemia is a risk factor for stroke, VCID, and AD; however, studies linking HHcy to neuropathologic hallmarks of dementia remain lacking. Previous studies have linked HHcy to changes in neuroimaging measures such as brain atrophy, white matter hyperintensities, and infarcts or cognitive performance, 30,31 while only a small number of studies have examined associations of HHcy with dementia‐related neuropathologies 27,32,33 . While there are a significant number of animal studies suggesting mechanisms for HHcy‐induced damage, there has been no robust human autopsy studies to evaluate these potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 5-aminovaleric acid, which is endogenously synthesized or derived from the metabolism of lysine by gut microbiota, is also known to act as a methylene homolog of gamma-aminobutyric acid (GABA) and functions as a weak GABA agonist [ 80 ]. Recently, 5-aminovaleric acid was identified in the plasma and brain tissues of Alzheimer’s disease patients [ 81 ]. It is currently unclear whether 5-aminovaleric acid could play a role in the stress response, presumably through synaptic modulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, more studies are needed to highlight its significance as an indication of TCA impairment [ 87 , 100 ]. Additionally, Kalecký et al also observed elevated levels of aconitic and succinic acids [ 101 ]. Another example of such a compound is acylcarnitines, whose plasma levels in AD patients are significantly higher than in controls.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%